PENGARUH EFIKASI DIRI DAN RESILIENSI GURU TERHADAP KETERLIBATAN KERJA GURU DI SDIT SE-KABUPATEN PADANG PARIAMAN - Ilham Suriadi; M Arif (Jurnal Manajemen Pendidikan, 2026)
This study aimed to examine the effect of teachers' self-efficacy on teacher work engagement, the effect of teachers' resilience on teacher work engagement, and the simultaneous effect of teachers' self-efficacy and resilience on teacher work engagement in Integrated Islamic Elementary Schools (SDIT) throughout Padang Pariaman Regency. The study employed a quantitative approach using an associative research design. The population consisted of 164 teachers, all of whom were selected as the research sample using the total sampling technique. Data were collected through a Likert-scale questionnaire that had met the requirements of validity and reliability. Data analysis was conducted using descriptive statistics, classical assumption tests, simple linear regression, and multiple linear regression with the assistance of SPSS version 22. The findings revealed that teachers' self-efficacy had a positive and significant effect on teacher work engagement. Similarly, teachers' resilience also had a positive and significant effect on teacher work engagement. Furthermore, teachers' self-efficacy and resilience simultaneously had a positive and significant effect on teacher work engagement in Integrated Islamic Elementary Schools (SDIT) throughout Padang Pariaman Regency. These findings indicate that the higher the levels of teachers' self-efficacy and resilience, the higher their level of work engagement. This study proposes an empirical model that integrates self-efficacy and resilience as psychological resources in explaining teacher work engagement within the context of Integrated Islamic Elementary Schools (SDIT), thereby contributing to the development of strategies for improving teacher performance through the enhancement of psychological resources.